Self-efficacy for writing and written text quality of upper secondary students with and without reading difficulties - Pär Sehlström; Christian Waldmann; Maria Levlin (Frontiers in Psychology, 2023)
IntroductionSelf-efficacy for writing (SEW) and reading ability are some of several factors that may be related to the quality of written text that students produce. The aim of the current study was (1) to explore the variation in SEW and written text quality in L1-Swedish and L2-English among upper secondary students with different reading profiles in L1 (typical reading vs. reading difficulties) and with different study backgrounds (SB1year or SB2years = one or two years of studies of Swedish and English, respectively), and in the next step (2) to explore if individual variations in L1-reading and SEW may explain variation in written text quality.MethodsParticipants were 100 upper secondary students (aged 17–18) with different reading profiles operationalized as typical reading and reading difficulties. Data consisted of screening for word recognition and reading comprehension, text quality results from argumentative L1- and L2-writing tasks, school information on study background in Swedish/English, and students’ responses from an online survey about SEW.ResultsAs to SEW results, an ANOVA revealed significant main effects for reading profile and study background in L1, but in L2 there was only a significant main effect for reading profile. Written text quality results indicated that there was a significant interaction effect between reading profile and study background in L1, indicating that the significant main effect for reading profile on written text quality was influenced by the group of students with reading difficulties and SB1year. There was a significant main effect for reading profile and study background on written text quality in L2. Students with reading difficulties and SB1year were the most vulnerable group, and they had the lowest scores in L1/L2 SEW and written text quality in L1 and L2. Multiple regression results indicated that word recognition and SEW contributed significantly to L1-text quality, and word recognition, reading comprehension, and SEW contributed significantly to L2-text quality. Thus, this study sheds light on the under-researched area of L1/L2 SEW and text quality of students with reading difficulties at the level of upper secondary school.DiscussionPedagogical implications are discussed and highlight the need for writing instruction across subjects in upper secondary school and for extra writing support/scaffolding for students with reading difficulties and shorter study background in the language subjects L1 (Swedish) and L2 (English).